Developing AtmoLearn: Mobile simulation learning media to enhance students understanding of atmospheric concepts - Fadlan, Muhammad Sainul Fadlan; Zulfa, Alfiatus; Handoyo, Budi (Bulletin of Educational Management and Innovation, 2025)
Background: The need for learning media continues to grow in accordance with students' learning needs, including in geography subjects. Geography material that still has difficulties in understanding is the phenomenon of the geosphere (Atmosphere). It is necessary to develop learning media that can solve problems in geography learning, namely media based on mobile learning simulation. Purpose: The purpose of this study is to develop a geography learning media product for atmospheric material based on mobile learning simulation in the form of a website with the product name AtmoLearn. Method: The development method used is a modification of ADDIE, namely ADD. Researchers are aware of limitations in implementing it.  Findings: The results of this study are to produce learning media products that are ready to be implemented. Thus, AtmoLearn products can be applied to students to determine their effectiveness, usefulness, and can increase student motivation and learning outcomes.